OPTIMIZATION OF INTEGRATED PLANTING COSTS USING THE KUHN TUCKER METHOD - Ika Thrisna Wahyu Dianti; Sajaratud Dur; Ismail Husein (Fakultas Keguruan dan Ilmu pendidikan (FKIP) Universitas Labuhan Batu, 2025)
The aim of this research is to seek optimization of rice planting costs using the method Kuhn Tucker. The method used in this research is method Kuhn Tucker. Method Kuhn Tucker is a method used to find the optimum point of a function without having to look at its linear or nonlinear properties. The solution to this method is to substitute it into the method Lagrange and must be given sufficient conditions Kuhn Tucker. Research results with methods Kuhn Tucker The Laswan Rice Refinery gets optimization of used costs with 24.96 Kg, 6.24 sacks of fertilizer, 3.7 Kg of pesticide and 1.3 HOK wages, so the optimal cost used is Rp. 11.875.370.00,- a hectare.Key Words: Kuhn Tucker Method, Lagrange Method, Optimization, Cost, Rice